Correlation between the Severity and Outcome of Acute Calculous Cholecystits According to Tokyo Guidelines - Thapa, Pradip; Adhikari, Krishna Mohan; Sharma, Anup (Journal of Nepalgunj Medical College, 2019)
Introduction: Acute Calculous Cholecystitis is a condition in which the gallbladder becomes inflamed due to cholelithiasis. Early diagnosis, severity grading and appropriate intervention reduce both morbidity and mortality. The aim of this prospective study is to correlate the severity with the outcome of acute calculous cholecystitis according to Tokyo Guidelines.Methods: This was a hospital based prospective study conducted in the Department of Surgery, Nepalgunj Medical College Teaching Hospital for a period of two years from April 2017 to March 2019. The patients were classified into three groups according to the severity grading in the Tokyo guidelines (TG18/ TG13). Clinical characteristics among these patients were analyzed for comparison.Results: Among all diagnostic criteria, right upper quarter (RUQ)h abdominal pain (94%) Murphy's sign (94%) and thickened gallbladder wall (80%) had the highest sensitivity rates (p